FACTORS THAT INFLUENCE THE INCOME OF AIR ITAM TRADITIONAL MARKET TRADERS, PANGKALPINANG CITY - yulia, yulia (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2025)
Income is a source of financing obtained by someone in the form of dividends, wages, salaries and profits. Looking at the condition of the Air Itam Traditional Market can tell you directly about the conditions in the field and will provide a direct picture of what factors influence the income of traders at the Air Itam Traditional Market. This research aims to: (1) determine the market conditions of the Air Itam Traditional Market in Pangkalpinang City, (2) determine the factors that influence the income of Air Itam Traditional Market traders in Pangkalpinang City. Using a survey method with a sample of 43 people from a total population of 158 traders at the Air Itam Traditional Market using the Harry King Nomogram with the Purposive Sampling method. The data in this research were analyzed quantitatively using descriptive methods and multiple linear regression. The results of this research show that (1) the condition of the Air Itam Traditional Market is quite clean and social interaction between traders and buyers is quite active, but public facilities are not available at the market. (2) factors that influence income are capital, type of business, length of business, and length of work of Air Itam Traditional Market traders